Admiral Peters : Odd Craft, Part 14. - Jacobs, W. W. (William Wymark), 1863-1943; Owen, Will, 1869-1957 (Salt Lake City, UT : Project Gutenberg, 2004)
"Admiral Peters" by W. W. Jacobs is a short story from the early 20th century that blends humor and social commentary. It revolves around the life of Mr. George Burton, a naval pensioner, and his unexpected encounter with an old friend, Joe Stiles. The main theme of the book centers on friendship, deception, and the complexities of relationships within a small-town setting. The story begins with Mr. Burton enjoying a quiet summer day when he is visited by his old shipmate, Joe Stiles, who is keen to rekindle their friendship. Stiles, claiming to have been an admiral, spins an exaggerated narrative that captivates Mrs. Dutton, a widow who owns a local shop and is attracted to the idea of an admiral. As Stiles' fanciful tales escalate, the line between truth and fiction blurs, leading to comedic situations as Burton struggles to maintain the facade while grappling with his friend$1 (Bs growing influence over Mrs. Dutton. The narrative culminates in a humorous resolution where the deception is finally put to rest, leaving Burton to navigate the fallout of his friend's antics. (This is an automatically generated summary.)s
Release date is 2004-04-01
Produced by David Widger
Keywords: Humorous stories, English; England -- Social life and customs -- Fiction; Sailors -- Fiction